METHODOLOGICAL ASPECTS OF THE TRAINING OF FORENSIC EXPERTS (PSYCHOLOGISTS AND CRIMINAL SPECIALISTS) TOWARDS PROFESSIONAL ACTIVITIES IN THE APPLICATION OF COMPLEX FORENSIC TECHNOLOGIES - Bohucharova Оlena (Distance Education in Ukraine: Innovative, Normative-Legal, Pedagogical Aspects, 2023)
The article deals with the methods, approaches of forming the basic forensic sciences’ competencies of future forensic police officers, forensic psychologists, lawyers in the process of professional training in a Ministry of Internal Affairs’ high schools with specific study conditions. Expertise and forensic systems of police criminalistic education are defined. The paper also demonstrates the role of specially created conditions for conducting high schools’ forensic technologies’ practical lessons (legal clinic, criminalistic laboratory, forensic training ground, training-laboratory, etc.). The difficulty of solving the problems of expertise didactics and high schools criminalistic’ education in the field of law is emphasized.